Establishing and Understanding Post-2020 Climate Change Mitigation Commitments - Briner, Gregory (OECD/IEA Climate Change Expert Group Papers, 2013)
A new international climate change agreement that will have legal force and be applicable to all countries is being negotiated under the auspices of the United Nations Framework Convention on Climate Change (UNFCCC). The agreement is to be adopted by 2015 and come into effect from 2020. An effective agreement would include quantitative mitigation commitments from all major emitters and result in concrete actions to reduce greenhouse gas emissions while catalysing long-term transformations to low-carbon and climate-resilient economies. The aim of this paper is to explore what mitigation commitments put forward under the 2015 agreement might look like, what guidance might be agreed regarding the type of commitments proposed, and which "rules of the game" would need to be agreed before draft commitments for the post-2020 period are put forward. The paper outlines what ex-ante information would need to be provided in order to understand commitments, and explores whether guidance could take the form of "bounded flexibility" for the various dimensions describing mitigation commitments in order to provide a basis for post-2020 emissions accounting and tracking progress. It also describes possible stages of the process for establishing commitments for the 2015 agreement